Characteristics of Cellulase Producing Bacteria Isolated from Gold Mine Soil - Fatmila Amirah Radwa; Nisa Rachmania Mubarik; Popi Asri Kurniatin (Institut Pertanian Bogor, 2026)
Land degradation has created an urgent need for innovative restoration strategies based on microbial applications. The microbiological approach using cellulase enzymes produced by cellulolytic bacteria is a prospective step to address problems related to land restoration and biodegradation of complex organic matter in the environment. This study aimed to isolate and characterize cellulolytic bacteria from post-mining soil collected at the Martabe gold mine site in South Sumatra, Indonesia. Isolation and selection of cellulolytic bacteria was performed on 1% carboxymethyl cellulose (CMC) medium, resulting of two non-pathogenic Gram-positive isolates, TSUS3.4.1 and TSUS3.4.2, with cellulolytic index of 2.51 and 2.26, respectively. Hemolysis tests on blood agar confirmed the semi- and non-pathogenic activity of both isolates. The growth curve and enzyme-specific activity was tested and measured in minimal nutrition broth with addition of 1% CMC with the highest activity values of 0.37 U/mg for TSUS3.4.1 and 0.17 U/mg for TSUS3.4.2 at the 27th hour after incubation. TSUS3.4.1 isolate has optimum cellulase activity at pH 6 and 30°C. TSUS3.4.2 isolate has optimum cellulase activity at pH 7 and temperature 30°C. These findings highlight the isolates potential positioning them as promising candidates for biotechnological applications in post-mining land rehabilitation and organic waste degradation. Keywords: biodegradation, cellulolytic bacteria, cellulose, organic matters, post-mining